(untitled) (AYUSHDHARA, 2025)
Avascular Necrosis of the Femoral Head is a progressive, debilitating condition characterized by the loss of blood supply to bone tissue, resulting in bone degeneration and joint dysfunction. It commonly affects young adults, and if left untreated, can result in long term disability and the need for joint displacement. The presentation of AVN is nearly similar to Gambheera Vatarakta, Asthimajjagata vata or Asthi kshaya depending on the course of the disease. Materials and Methods: A male patient aged 35 years presented pain in right hip joint which was associated with stiffness since 1 year 2 months was diagnosed as bilateral Avascular necrosis of femoral head. The patient was treated in 3 phases where Manjistadi Kashaya seka, Vankshana basti, Manjistadi kshara followed by Ksheera basti was done. Results: Clinical outcomes were assessed using pain scales, range of motion and MRI imaging. There was significant improvement in overall symptoms. Conclusion: Conventional treatments often include pharmacological management, core decompression or surgical intervention. This case reports deals with a detailed information regarding Panchakarma treatment in managing AVN of the femur.